European Arrest Warrant - Klimek, Libor (Springer, 2015)
This book examines the European arrest warrant as a successful and effective instrument for judicial co-operation in criminal matters in the European Union. Providing comprehensive content and combining theoretical and practical aspects, it covers all of the major issues surrounding the European arrest warrant. The book analyses its genesis, main features, surrender procedure, case law, implementation and the latest developments. Instead of focusing solely on a criminal law approach, it also considers the subject from the perspective of European Union law and constitutional law.